Synthesis, physical and chemical properties of esters of 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazole-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazole-3-yl)thio)methyl)benzoic acids - А. M. Rud; A. G. Kaplaushenko; Yu. M. Kucheryavyi; Fadi Al Zedan (Zaporozhye State Medical University, 2017)
The wide use of 1,2,4-triazole derivatives in medical practice is primarily explained by two most important properties: high biological activity and low toxicity. It is difficult to overestimate the contribution to medical practice, which such medicines as posaconazole and letrozole have made. Many scientists of the pharmaceutical industry pay attention to the search of biologically active substances among this heterocyclic system derivatives. Aim. The aim of our study is purposeful synthesis of new highly effective and low-toxic substances among the derivatives of 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)methyl)benzoic acids, the study of their physical and chemical properties. Materials and methods. The 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)methyl) benzoic acids were used as initial substances, which were obtained at the previous stage of synthesis. The esters were synthesized by the esterification of 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)methyl)benzoic acids in the appropriate alcohol medium with the addition of concentrated sulfuric acid in catalytic amoun. Results. The structure of obtained compounds was established using a complex of modern physical and chemical analysis methods. The experimental determination of the elemental composition of the obtained substances corresponds to the calculated data. The only one peak was detected on the chromatograms of synthesized esters, which corresponds to the calculated molecular weight m/z+ of series compound. The IR-spectra of the synthesized compounds have the absorption bands of the C-S groups, absorption bands of the aromatic ring, symmetric and asymmetric absorption bands of the C-O-C groups and they fit with reference data. The 1H NMR spectra have proton signals of methyl and methylene groups of the obtained compounds. It ultimately confirms the structure of the synthesized compounds. Conclusions. We have developed effective laboratory methods for the preparation of esters of 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triasole-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazol-3-yl)thio)methyl)benzoic acids during the experimental work. Thirteen new compounds were synthesized which are now the objects of further pharmacological researches.